R-star: A new approach to estimate the polar star of monetary policy - Peter Bofinger; Thomas Haas (University of Würzburg, Department of Economics, 2023)
The necessary adjustments to prominent measures of the neutral rate of interest following the COVID pandemic sparked a wide-ranging debate on the measurement and usefulness of r-star. Due to high uncertainty about relevant determinants, trend patterns and the correct estimation method, we propose in this paper a simple alternative approach derived from a standard macro model. Starting from a loss function, neutral periods can be determined in which a neutral real interest rate is observable. Using these values, a medium-term trend for a neutral interest rate can be determined. An application to the USA shows that our simple calculation of a neutral interest rate delivers comparable results to existing studies. A Taylor rule based on our neutral interest rate also does a fairly good job of explaining US monetary policy over the past 60 years.
urn:nbn:de:bvb:20-opus-327394
Keywords: E3; E4; E5; 330; Neutral rate of interest; equilibrium real interest rate; monetary policy rul